Dual-Specificity Phosphatase 14 Regulates Zebrafish Hair Cell Formation Through Activation of p38 Signaling Pathway - Wei, Guanyun; Zhang, Xu; Cai, Chengyun; Sheng, Jiajing; Xu, Mengting; Wang, Cheng; Gu, Qiuxiang; Guo, Chao; Chen, Fangyi; Liu, Dong; Qian, Fuping (Frontiers in Cellular Neuroscience, 2022)
Most cases of acquired hearing loss are due to degeneration and subsequent loss of cochlear hair cells. Whereas mammalian hair cells are not replaced when lost, in zebrafish they constantly renew and regenerate after injury. However, the molecular mechanism among this difference remains unknown. Dual-specificity phosphatase 14 (DUSP14) is an important negative modulator of mitogen-activated protein kinase (MAPK) signaling pathways. Our study was to investigate the effects of DUSP14 on the supporting cell development and hair cell regeneration and explore the potential mechanism. Our results showed that dusp14 gene is highly expressed in zebrafish developing neuromasts and otic vesicles. Behavior analysis showed that dusp14 deficiency resulted in hearing defects in zebrafish larvae, which were reversed by dusp14 mRNA treatment. Moreover, knockdown of dusp14 gene caused a significant decrease in the number of neuromasts and hair cells in both neuromast and otic vesicle, mainly due to the inhibition of the proliferation of supporting cells, which results in a decrease in the number of supporting cells and ultimately in the regeneration of hair cells. We further found that significant changes in a series of MAPK pathway genes through transcriptome sequencing analysis of dusp14-deficient zebrafish, especially mapk12b gene in p38 signaling. And inhibiting p38 signaling effectively rescued all phenotype caused by dusp14 deficiency, including hair cell and supporting cell reduction. These results suggest that DUSP14 might be a key gene to regulate supporting cell development and hair cell regeneration and is a potential target for the treatment of hearing loss.